(untitled) (New York, 1968)
Most of the essays presented in this book were papers prepared for a conference on the language problems of the developing nations at Airlie House, Warrenton, Virginia, November 1-3, 1966
Keywords: Quốc gia đang phát triển,Developing countries,Sociolinguistics,Ngôn ngữ học xã hội; Ngôn ngữ,Languages